2017
DOI: 10.1089/jayao.2016.0013
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Case Report: Yoga for Fatigue in Five Young Adult Survivors of Childhood Cancer

Abstract: Purpose: Cancer-related fatigue (CRF) is a distressing consequence of cancer and its treatment. CRF impacts many young adult (YA) survivors of childhood cancer, compromising work, social relationships, and daily activities. No satisfactory treatment exists. This pilot study aimed to assess the feasibility, safety, and preliminary efficacy of an 8-week twice/week Iyengar yoga (IY) intervention for treating persistent fatigue in YA survivors of childhood cancer. Methods: Using a single-arm mixed-methods design, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 27 publications
0
26
0
Order By: Relevance
“…Vitality among patients with cancer was reported in 38 (13.8%) of included studies, most often as a component of overall quality of life or well-being. Few factors were reported that increased vitality, including marriage, 116 yoga, 117 and stronger overall mental or physical health. 118 , 119 There were conflicting results for whether time since diagnosis improves vitality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitality among patients with cancer was reported in 38 (13.8%) of included studies, most often as a component of overall quality of life or well-being. Few factors were reported that increased vitality, including marriage, 116 yoga, 117 and stronger overall mental or physical health. 118 , 119 There were conflicting results for whether time since diagnosis improves vitality.…”
Section: Resultsmentioning
confidence: 99%
“…54,103 Mind-body exercises, like yoga and tai-chi, improved self-acceptance, and, according to patients, this occurred by demonstrating their body's physical capabilities were intact. 33,117 Happiness was studied by 14 (5.1%) included articles. The factors most commonly attributed to increased happiness was the cancer experience and the suffering it caused, 94 the relief of completing treatment, 160 and gratitude for suffering less than expected.…”
Section: Fig 2 Word Cloud Of Constructs and Their Frequency In Inclmentioning
confidence: 99%
“…Recently, attention has been focused on perception-based components of pain because of their ability to reduce pain via nonpharmacologic behavioral techniques, such as guided imagery, mindfulness and relaxation training, hypnosis, and cognitive behavioral therapy. [35][36][37] Chronic pain and central sensitization in SCD…”
Section: Somatosensory System and Generation Of Painmentioning
confidence: 99%
“…Yoga can improve disease- and treatment-related side effects in cancer survivors by addressing physical, psychological, and spiritual needs. Although limited, research supports quality of life benefits in YA childhood cancer survivors 5 as well as in adult, noncurative cancer patients. 6 To date, no study has explicitly explored the potential benefits of yoga for YAs with a noncurative cancer diagnosis.…”
Section: Introductionmentioning
confidence: 99%